2002
DOI: 10.1073/pnas.152342999
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule inhibitor of the ribonucleolytic activity of human angiogenin that possesses antitumor activity

Abstract: The results of previous preclinical and clinical studies have identified angiogenin (ANG) as a potentially important target for anticancer therapy. Here we report the design and implementation of a high-throughput screening assay to identify small molecules that bind to the ribonucleolytic active site of ANG, which is critically involved in the induction of angiogenesis by this protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
165
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 38 publications
3
165
0
2
Order By: Relevance
“…Mutagenesis analyses have shown that reducing the ribonucleotic activity of ANG also reduced its angiogenic properties (85)(86)(87)(88)(89)(90). N65828, an inhibitor of ANG ribonucleotic activity, inhibited PC-3 prostate tumor cell oncogenesis as well as a model of AKT-induced prostate intraepithelial neoplasia in vivo (84,91). Neomycin has been previously shown to inhibit ANG nuclear translocation and consequently to reduce ANG-induced cell proliferation and angiogenesis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis analyses have shown that reducing the ribonucleotic activity of ANG also reduced its angiogenic properties (85)(86)(87)(88)(89)(90). N65828, an inhibitor of ANG ribonucleotic activity, inhibited PC-3 prostate tumor cell oncogenesis as well as a model of AKT-induced prostate intraepithelial neoplasia in vivo (84,91). Neomycin has been previously shown to inhibit ANG nuclear translocation and consequently to reduce ANG-induced cell proliferation and angiogenesis (44).…”
Section: Discussionmentioning
confidence: 99%
“…A constituent of normal plasma (6) and milk (7), it is secreted by a wide variety of normal cells (3,8) including those of the placenta (9,10). It has received much attention because of its involvement in the growth of tumors (11)(12)(13)(14)(15). Its expression level is elevated in pancreatic and several other types of cancers (15).…”
mentioning
confidence: 99%
“…It has received much attention because of its involvement in the growth of tumors (11)(12)(13)(14)(15). Its expression level is elevated in pancreatic and several other types of cancers (15). Antagonists of hAng block tumor growth and metastasis (of prostate cancers in particular) (11)(12)(13)(14)(15), identifying it as a promising target for anticancer therapy.…”
mentioning
confidence: 99%
“…This list was supplemented with compound classes containing 66 compounds published as bioactive in various assays of this library. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] To identify compound classes with side effects (having multiple targets), compound classes scoring positively in two or more pure protein assays or scoring positively in an assay for fluorescence and another assay employing a nonfluorescent readout were identified. The compounds identified as bioactive and the classes containing them generally only had a single reported target and were assumed to be specific since many of these compounds were previously evaluated for side effects prior to their publication or were optimized structurally: this does not preclude the possibility that secondary targets of these compounds may be observed at higher compound concentrations or in other biological assays not tested; but for the sake of this comparison, they will be labeled as "single target" classes.…”
Section: Methodsmentioning
confidence: 99%